Programming education with a blocks-based visual language for mobile application development - (:unkn) unknown (IADIS, 2014)
The aim of this study is to assess the impact upon academic success of the use of a reference block-based visual programming tool, namely the MIT App Inventor for Android, as an educational instrument for teaching object-oriented GUI-application development (CS2) concepts to students; who have previously completed a fundamental programming course that involved education of structured programming concepts using C# (CS1). It has also been studied whether impacts upon CS2 success of factors such as previous success in CS1 and prior high school experience in programming, have a relationship with the impact upon CS2 success from the use of the blocks-based instructional tool. The research; which has a post-test only quasi-experimental design; has a sample comprised of 101 Undergraduate students who are taking up the CS2 course at a Department of Computer Education and Instructional Technologies (CEIT). © 2014 IADIS.
Keywords: App inventor; Mobile application development; Programming blocks; Programming education; Programming paradigms